Risk Factors of Salvage Procedure for Refractory Morcellation During Holmium Laser Enucleation of the Prostate - Hyun Sik Yoon; Dae Hyuk Chung; Sung Yong Cho; Min Chul Cho; Jae-Seung Paick; Seung-June Oh (International Neurourology Journal, 2023)
Purpose We aimed to identify the risk factors for salvage procedure (SP) required for refractory adenomatous tissue resistant to morcellation during holmium laser enucleation of the prostate (HoLEP). Methods Patients who underwent HoLEP between January 2010 and April 2020 at Seoul National University Hospital were analyzed. SPs were defined as cases of conversion to resection of the prostatic tissue using an electrosurgical loop after morcellation or secondary morcellation a few days after surgery or conversion to open cystotomy. Results Among a total of 2,427 patients, 260 were identified as having SP (SP group) (transurethral resection-nodule [n = 250, 96.1%], secondary morcellation a few days after surgery [n = 9, 3.5%], and conversion to open cystotomy [n = 1, 0.4%]). Patients in the SP group were older and had higher 5-α reductase inhibitors use, higher prostate-specific antigen, larger total prostate volume, and larger transition zone volume (TZV) than those in the non-SP group. In the multivariable logistic regression analysis, only age and TZV were associated with SP. Compared to 40s and 50s, the odds ratios (ORs) were 3.84 in 60s (95% confidence interval [CI] 1.37–10.78, P = 0.011), 4.53 in 70s (95% CI, 1.62–12.62, P = 0.004), and 6.59 in 80s or older (95% CI, 2.23–19.46, P = 0.001). The ORs of the SP were analyzed per TZV quartile. Compared to TZV ≤ 20.3 mL, the OR was 3.75 in 32.0 mL < TZV ≤ 50.4 mL (95% CI, 2.00–7.04, P < 0.001) and 8.25 in 50.4 mL < TZV (95% CI, 4.06–16.77, P < 0.001). Conclusions The risk of refractory morcellation increased in patients aged > 60 years or those with TZV > 32 mL. In order to more efficiently remove these resistant adenomas, it is necessary to develop more efficient morcellators in the future.